DEVELOPING LEARNING MEDIA BY USING BASIC ENGLISH GRAMMAR POCKET BOOK - Anam, Mukhtarul; Setyaningrum, Riya Risqi; Fatmawaty, Riryn; Labibah, Faridatul (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2023)
The objective of this research is to develop learning materials for the precise understanding of Basic Grammar in English, in the form of a Pocket Book, specifically designed for eighth-grade students at MTs Bustanul Ulum, Glagah, Lamongan. The research employed a developmental research approach, consisting of ten stages: Need Survey, product design, design validation, design revision, try out 1, product revision, try out 2, product revision, and final product. The developed product underwent review by a supervisor, Media Expert, and Material Expert, and was evaluated by 15 students from MTs Bustanul Ulum. The research instruments included a questionnaire for the Validators, a questionnaire for student feedback, and an interview guide for the teacher to analyze the students' results. The students' responses were analyzed using both quantitative and qualitative methods, with the quantitative analysis used for calculating the results and the qualitative analysis employed for interviews, critiques, and suggestions. The findings indicated that the students required a supportive book for learning English with simple explanations and comprehensibility. The outcome of this study was the creation of a Basic English Grammar Pocket Book. The researcher suggests that this product can be utilized in the learning process for an extended period as it facilitates easy studying and allows students to carry the book everywhere they go.